Seroprevalence and Seroconversion of Dengue and Implications for Clinical Diagnosis in Amazonian Children - Martins, Antonio Camargo; Pereira, Thasciany Moraes; Oliart-Guzmán, Humberto; Delfino, Breno Matos; Mantovani, Saulo Augusto Silva; Braña, Athos Muniz; Branco, Fernando Luiz Cunha Castelo; Filgueira Júnior, José Alcântara; Santos, Ana Paula; Ramalho, Alanderson Alves; Guimarães, Andréia Silva; de Araújo, Thiago Santos; et al. (Interdisciplinary Perspectives on Infectious Diseases, 2014)
This study aimed to evaluate the prevalence of serum IgG dengue in children in an Amazonian population, to assess the seroconversion rate in 12 months, and to estimate how many seropositive children had a prior clinical diagnosis of dengue. We conducted a population-based study between 2010 and 2011, with children aged 6 months to 12 years that were living in the urban area of a small town in the Brazilian Amazon. The prevalence of IgG antibodies against dengue antigens was determined by indirect ELISA technique, and seronegative children were reexamined after 12 months to determine seroconversion rates. Results showed seroprevalence of IgG antibodies against dengue type of 2.9%, with no significant association between age, race, and sex. In seropositive children, only 8.4% had received a clinical diagnosis of dengue, and the ratio of clinically diagnosed cases and subclinical cases was 1 : 11. The seroconversion rate between 2010 and 2011 was 1.4% (CI 3.8% to 35.1%). The seroprevalence of dengue in this pediatric population was low, and the vast majority of cases were not clinically detected, suggesting a difficulty in making the clinical diagnosis in children and a high frequency of asymptomatic infections.